Sentiment Analysis of Telkom University as the Best BPU in Indonesia Using the Random Forest Method - Irfan Budi Prakoso; Donni Richasdy; Mahendra Dwifebri Purbolaksono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In this day and age, social media has become a necessity for every human being. By using social media networks, users can easily exchange information, especially on linkedin social media. Linkedin is a social media network that can search for information openly, mainly used for professional networking. It will be easier and more practical to connect with professionals worldwide. Like identity, LinkedIn is often used as a medium to introduce yourself or your business to potential colleagues or companies for various purposes. Social media networks are often used to deliver information in various institutions at State Universities (PTN) and Private Universities (PTS). For example, it conveys information about state and private universities' achievements (PTS) achievements. Telkom University uses Linkedin to convey the achievements that have been achieved. This triggers the public to see posts that are positive, negative, or neutral. This study aims to conduct a sentiment analysis about Telkom University which has become the best private university in Indonesia, based on opinions submitted on LinkedIn social media. The process carried out in this study is to process all opinion data about Telkom University, which is the best private university in Indonesia, from Linkedin and then classification using the Random Forest method based on the categories of positive, neutral, and negative sentiments. Sentiment analysis results that have been obtained using the Random Forest classification method are 92.85% accuracy, 83.33% precision, 91.67% recall, and 84.13% F1-score%.